LIQUID MODERNITY IN HYPERTEXT LITERARY FRAME “BREATHING AT THE GALAXY’S EDGES” - Dewi, Marisa Santi; Zuliana, Rina; Salam, Aprinus (Prosiding Konferensi Internasional Kesusasteraan, 2025)
This study aims to explore the textual and contextual features of hypertext literature in framing liquid modernity as a social phenomenon. Hypertext poem “Breathing at the Galaxy's Edges” as the main object of exploration on framing liquid modernity. Zygmunt Bauman's perspective on liquid modernity is applied to identify how literature frames the phenomenon. Liquid modernity represents the nature of an ever-moving, flowing, flexible, temporary, and uncertain era. This study analyzes the data by comparing the literary text with the context of liquid modernity. The textual approach identifies ambivalence, metaphors, and metonymy. The contextual method was carried out by comparing the text, reading techniques, and the current social context of society. The results show that hypertext literature frames the era of liquid modernity textually, practically, and contextually. The poetry texts reveal the infinite nature of human life, which leads them to void, loneliness, and unconsciousness about who they are and who they are facing. In addition, the non-linear practice of reading poetry offers uncertainty, emancipation, and individuality. Thus, the context shows that social life is no longer determined. Humans are free to define their identity, life, and what they want to do. However, they must bear the consequences themselves.